Analysis of Financial Management of Village-Owned Enterprises (BUMDes) Based on Government Regulation Number 11 of 2021 (Case Study in Niampak Village, Beo Selatan District, Talaud Islands Regency) - Maradesa, Maya Veronicha; Tinangon, Jantje J.; Kapojos, Peter M. (Formosa Journal of Science and Technology, 2025)
This research aims to determine the financial management of the Village-Owned Enterprise (BUMDes) Tinarangen in Niampak Village, South Beo District, Talaud Islands Regency. The research method used is qualitative with descriptive analysis. Data collection techniques are observation, interviews, and documentation. The data sources in this research are primary and secondary data. This research is guided by Government Regulation No. 11 of 2021 concerning Village-Owned Enterprises, wich seen from the process of planning, implementation, and accountability. The result of the research show that (1) Planning at BUMDes Tinarangen is discussed and agreed upon during village meetings; (2) Implemetation of BUMDes Tinarangen are carried out by the operational executor, where the in recording records BUMDes Treasurer only records cash expenditures in the daily cash book, while cash income are not recorded. The financial reports are prepared by the BUMDes supervisor due to the Treasurer's limitations in preparing financial reports; (3) The accountability of BUMDes Tinarangen, since it started operating until now has only been to the BUMDes Supervisor and is only verbal accountability.